Acupoint injection therapy for diabetic retinopathy: A protocol for systematic review and meta-analysis. Issue 1 (8th January 2021) - Zhou, Yanni; Li, Hui; Luo, Lisi; Chen, Yue; Chen, Qiang; Bian, Wei; Yang, Yanlin; Tang, Ju
Abstract: Background: Diabetic retinopathy (DR) is a common diabetic microvascular complication, and it is also the main cause of blindness in adults. At present, some studies have reported acupoint injection for the treatment of DR. However, the effectiveness and safety are still uncertain. This study aims to evaluate the efficacy and safety of acupoint injection for the treatment of patients with DR. Methods: The databases of English databases (PubMed, Embase, Cochrane Library, Web of Science) and Chinese databases (China National Knowledge Infrastructure, Chinese Scientific Journal Database, Wanfang Database, and Chinese Biomedical Literatures Database) will be retrieved. Published randomized controlled trials and quasi-randomized controlled trials on the topic will be retrieved by 2 investigators independently. We will apply a fixed-effect model or random effect model basis on the heterogeneity test and employ with RevMan 5.3 software for data synthesis. The total effective rate will be selected as the primary outcome, visual acuity, hemorrhage areas, exudates, capillary nonperfusion areas, hemorheological indicators, mean defect of visual field, glycated hemoglobin, and adverse events as secondary outcomes. Results: This study will comprehensively summarize the high-quality trials to determine the effectiveness and safety of acupoint injection treatment for patients with DR. Conclusion: The systematic review of this study will summarize the currently published evidence of acupoint injection treatment for DR to further guide its promotion and application. Protocol registration number: INPLASY2020110026